Test Study on Performance of Endothermic Highly Hydrophobic Anti-Icing Materials. (October 2020) - Peng, Yongjing; Fang, Zhen; Hu, Jianping; Wang, Bowen; Xie, Pengkang
Abstract: In this paper, the solar spectrum selective endothermic coating with CoCuMnOx as the light absorbing pigment is prepared to absorb sunlight efficiently. After optimizing the thickness of the coating, the endothermic coating material with absorptivity of 0.928 and emissivity of 0.198 is obtained. The roughness value of the coating is 0.64 μm, which ensures that the coating has a higher sunlight absorption rate without the need for an antireflection layer. Icing flashover tests were carried out on insulators coated with endothermic highly hydrophobic anti-icing materials. The ice lightning voltage of ceramic insulators (3 pieces) was increased by 13.68%, and that of glass insulators (2 pieces) was increased by 22.96%. Compared with ceramic insulators, glass insulators coated with anti-icing materials have better protection effect.